Manajemen Pemasaran Pendidikan Dalam Peningkatan Kuantitas Peserta Didik - M. Munir (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2018)
: Marketing can not be sep arated from management activities, because marketing management is in charge of how a school effort reaches its predetermined objectives in its marketing, such as promoting schools to satisfy consumers and quality services. A school needs to pay attention to its marketing management because that will determine how many learners will enroll in the school. But in marketing education that must be considered not only outside the school just like the installation of banners or the spread of brochures but also must be revamping from within the school, especially in the revamping of its resources. Because with the existence of quality resources, will give birth image or good image in the eyes of society. Most parents choose schools that already have a good image or image in the community. Their main focus is on the educational processes that occur during school, teaching and learning activities, and the quality of school services. By providing excellent service or excellent service is one effort to grow consumer confidence. If the learner is likened to the consumer, then it takes various efforts to provide the best service so that they can learn optimally especially in school. Costumer satisfaction or customer satisfaction is preferred in business activities, as well as in education, although not business, services to learners should always take precedence. Services for learners not only from teachers, but also from the administrative staff. In this case, in the event of things that may reduce the service, the principal must immediately take positive steps to restore confidence to normal. Satisfaction of learners as customers will be able to increase the prestige of the school so it will be liked by the community and eventually become a favorite school. Excellent service is the main purpose and capital to attract learners and potential learners. What is suggested in the business world may be appropriate, that in order to achieve customer satisfaction, it needs to be close to the consumer (close to the costumer) in addition to the strong desire of the principal to make his school a hands-on value driven. Service is also not half-baked, but must be (hands on the knitting) so that learners as the party served feel satisfied (costumer satisfaction), which will increase confidence in the school